2016
DOI: 10.1097/ta.0000000000001122
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary injuries and extremity amputation in Operations Enduring Freedom and Iraqi Freedom

Abstract: Epidemiologic/prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…15 Regarding GU complications, Nnamani et al reported that low testosterone was common in participants with GU injuries, sometimes resulting in sexual dysfunction and difficulty in completing ADLs. 24 Another study by Metze et al found that in polytraumatized participants, other conditions like spinal cord lesions, traumatic brain injury, hand injuries, anxiety, depression, and pelvic pain all contributed to sexual dysfunction. 25 The nature of limb loss at the hip and pelvic level has major implications on the GI and GU systems, especially in the setting of IED blasts because of a lack of sufficient body armor in this area.…”
Section: Gi and Gu Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Regarding GU complications, Nnamani et al reported that low testosterone was common in participants with GU injuries, sometimes resulting in sexual dysfunction and difficulty in completing ADLs. 24 Another study by Metze et al found that in polytraumatized participants, other conditions like spinal cord lesions, traumatic brain injury, hand injuries, anxiety, depression, and pelvic pain all contributed to sexual dysfunction. 25 The nature of limb loss at the hip and pelvic level has major implications on the GI and GU systems, especially in the setting of IED blasts because of a lack of sufficient body armor in this area.…”
Section: Gi and Gu Functionmentioning
confidence: 99%
“…25 The nature of limb loss at the hip and pelvic level has major implications on the GI and GU systems, especially in the setting of IED blasts because of a lack of sufficient body armor in this area. 24,26 The most frequent locations of operation after IED blasts are the testis (20.6%), bladder (18.9%), scrotum (17.8%), and the kidneys (13.5%). 24…”
Section: Gi and Gu Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these patients do not have adequate donor sites for the flaps and are missing soft tissue, and recipient vessels, and so on at the recipient sites. Because of the perineal damage caused by blast injuries, many wounded warriors lack the eligibility for a phalloplasty [10]. The emerging concept of GUVCA holds significant promise for such patients, and is exemplified by the remarkable GUVCA performed by Redett's group at Johns Hopkins on such a patient with genitourinary tissue loss and extensive abdominal, and perineal tissue loss, who received the most complex GUVCA to date.…”
Section: Current Reconstructive Optionsmentioning
confidence: 99%
“…Finally, genitourinary injuries may result from penetrating and blast trauma both within both the civilian and military population. Review of the Department of Defense Trauma Registry from October 2001 through August 2013 found 1,367 service members with genitourinary injuries, with 31% involving the penis (18). …”
Section: Introductionmentioning
confidence: 99%